2007
DOI: 10.1080/13607860600844424
|View full text |Cite
|
Sign up to set email alerts
|

Assessing late-onset stress symptomatology among aging male combat veterans

Abstract: This study's goal was to develop a measure of late-onset stress symptomatology (LOSS). LOSS is a phenomenon observed in aging combat veterans who (a) were exposed to highly stressful combat events in their early adult years, (b) have functioned successfully throughout midlife with no history of chronic stress-related disorders, but (c) begin to register increased combat-related thoughts, feelings, and reminiscences commensurate with the changes and challenges of aging. Several samples of older male combat vete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 59 publications
2
51
1
Order By: Relevance
“…Studies focusing on combat veterans have found that aging can induce delayed-onset PTSD years after the initial combat trauma (for a review, see Averill & Beck, 2000). Several studies have also found symptoms congruent with LOSS in combat veterans as they age (Davison et al, 2006;King et al, 2007). Studies examining the well-being of aging Holocaust survivors have also found high levels of emotional and psychological distress, including depression, suicide, and PTSD (Barak et al, 2005;Kahana, Harel, & Kahana, 2005;Trappler, Cohen, & Tulloo, 2007).…”
Section: The Intersection Of Trauma and Agingmentioning
confidence: 93%
“…Studies focusing on combat veterans have found that aging can induce delayed-onset PTSD years after the initial combat trauma (for a review, see Averill & Beck, 2000). Several studies have also found symptoms congruent with LOSS in combat veterans as they age (Davison et al, 2006;King et al, 2007). Studies examining the well-being of aging Holocaust survivors have also found high levels of emotional and psychological distress, including depression, suicide, and PTSD (Barak et al, 2005;Kahana, Harel, & Kahana, 2005;Trappler, Cohen, & Tulloo, 2007).…”
Section: The Intersection Of Trauma and Agingmentioning
confidence: 93%
“…This investigation was conducted as a supplement to the previous study of LOSS (King et al, 2007). To lend additional support to findings suggesting that LOSS is a construct distinct from PTSD, our present goal was to further assess the discriminant validity of the LOSS Scale.…”
Section: Introductionmentioning
confidence: 94%
“…Guided by Davison et al (2006) conceptualization of LOSS, King, King, Vickers, Davison, and Spiro (2007) developed the LOSS Scale (published in this journal) and demonstrated its reliability and validity in a sequence of studies using multiple samples of aging veterans. One finding was that scores on the LOSS Scale and the PTSD Checklist -Civilian Version (PCL-C; Weathers, Litz, Herman, Huska, & Keane, 1993) were only moderately associated, with shared variance just below 50%.…”
Section: Introductionmentioning
confidence: 99%
“…Constant repetition of stress gradually depletes coping resources and makes the veteran more vulnerable to subsequent stressors. This may lead to depression, combat stress reaction, and, for some, PTSD (Briere, 2004) or in later years, Late Onset Stress Symptomatology (Andrews, Brewin, Philpott, & Stewart, 2007;Davison et al, 2006;L. A.…”
Section: Discussion and Implications For Practicementioning
confidence: 99%